Development of Tutorial System on Text Mining Skill for Users of TETDM - KAWAMOTO, Kayo; NAKAGOCHI, Rina; NISHIHARA, Yoko; SUNAYAMA, Wataru (Journal of Japan Society for Fuzzy Theory and Intelligent Informatics, 2015)
Data analysis with text mining is now attracting many people. Many softwares of text mining are also available. Users of text mining softwares need to acquire text mining skills to select and operate tools, to analyze data, and so on. In order to acquire the skills, users have to be assigned exercises about selection and operation of suitable tools, and interpretation of analyzed data. So, this paper proposes a tutorial system for users to acquire the text mining skills with a software TETDM. The tutorial system gives users exercises. The exercises are ordered according to its level: basic one is arranged in the former and advanced one is in the latter. We evaluated the proposed tutorial system in an evaluation experiment. It was confirmed that the subjects of the experiment could have acquired text mining skills with TETDM by the tutorial.